Development of problem-solving based test instruments to foster the students creative thinking skills on environmental conservation - Annissa Dwi Rizkia; Sjaifuddin Sjaifuddin; Dwi Indah Suryani (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram, 2022)
This study aims to obtain data on the feasibility of problem-solving-based test instruments to foster the creative thinking skills of junior high school students on environmental conservation. The method used in this study is Research & Development (R&D) with development procedures according to Sugiyono. This study was conducted in 5 stages: potentials and problems, data collection, product design, design validation, and design revision. The instrument used in this development research is a question validation sheet of material experts, evaluation experts, and expert practitioners. The results showed that based on the assessments of content experts, evaluation experts, and practitioners, scores of 88.4%, 88.6%, and 89.9% were obtained, which were classified in the